Modern blood banking & transfusion practices - Harmening, Denise (Philadelphia : F.A. Davis Company, 2019)
Join the generations of students who have embarked on successful careers with a firm foundation in the theory and practice of blood banking and transfusion practices. Denise Harmening's classic text teaches you not only how to perform must-know tests and tasks, but to understand the scientific principles behind them
1. Fundamentals concepts -- 2. Blood groups and serologic testing -- 3. Transfusion practices -- 4. Leukocyte antigens and relationship testing -- 5. Quality management and compliance
Includes bibliographical references and index
Keywords: Blood Banks -- methods; Blood Grouping and Crossmatching; Blood -- Transfusion